The Effectiveness of Using Picture as Media Towards Students’ English Speaking Skills - Fitri Wahyuni Manurung; Dahlia Sirait (Education & Learning, 2023)
The objective of this research was to find out the effectiveness of using picture as media towards students' English speaking skills. This research was conducted at MAS Al-Manar Medan in the academic year 2022/2023. The samples of this research were 37 students of class XI IPA and IIS. This research was conducted using an experimental research design with two classes, the experimental class consisting of 19 students and the control class consisting of 18 students. The experimental group was given pre-test, treatment and post-test and the control group was given pre-test and post-test. The instrument of this research was an oral test, which was given in the pre-test and post-test. The results of this research showed that the t-observed value was higher than the t-table (15.288 > 2.030). The alternative hypothesis was accepted. It means that the effectiveness of using picture as media significantly affected towards students' English speaking skills.